Data quality the accuracy dimension - Olson, Jack E. (San Francisco : Morgan Kaufmann, 2003)
Data Quality: The Accuracy Dimension is about assessing the quality of corporate data and improving its accuracy using the data profiling method. Corporate data is increasingly important as companies continue to find new ways to use it. Likewise, improving the accuracy of data in information systems is fast becoming a major goal as companies realize how much it affects their bottom line. Data profiling is a new technology that supports and enhances the accuracy of databases throughout major IT shops. Jack Olson explains data profiling and shows how it fits into the larger picture of data quality. * Provides an accessible, enjoyable introduction to the subject of data accuracy, peppered with real-world anecdotes. * Provides a framework for data profiling with a discussion of analytical tools appropriate for assessing data accuracy. * Is written by one of the original developers of data profiling technology. * Is a must-read for any data management staff, IT management staff, and CIOs of companies with data assets.
The data quality problem -- Definition of accurate data -- Sources of inaccurate data -- Data quality assurance -- Data quality issues management -- The business case for accurate data -- Column property analysis -- Structure analysis -- Simple data rule analysis -- Complex data rule analysis -- Value rule analysis.
Includes bibliographical references (p. 279-281) and index.
Keywords: Database management -- Quality control; Electronic books